Simulación del proceso de obtención de azúcares fermentables a partir del hidrolizado de bagazo de caña de azúcar para la producción de xilitol (2020)
Sugarcane bagasse production around the world has increased especially in Colombia and Brazil, these countries have different ways to obtain sub products with this residue such as bioethanol, electricity by sugarcane incineration, and xylitol by the biological transformation Xylitol is of great interest due to its application in the food industry and pharmaceutics industry. The main objective of this work is to create a simulation of the hydrolysis of the xylitol production using Aspen Plus® and compare these results with the published data by the Group of Microbiology applied to Bioprocess (GMBIO) in the Escola de Engenharia de Lorena Universidade de Só Pablo (EEL-USP). Published papers from GMBIO were revised to compile information about process routes, unit operations, operation conditions, and yields of compounds of interest and to have insights for the simulation. As a result, energy requirements and operating conditions for the hydrolysis unit, concentration process, neutralization...